DETERMINANTS OF INDONESIA’S TRADE BALANCE : A VECM MODEL APPROACH - Indrasari, Dhea Rahmanda; Soelistyo, Aries; Anjaningrum, Widiya Dewi (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2024)
Trade Balance is the main indicator in external competitiveness. The condition of the trade balance in Indonesia tends to experience unbalanced conditions every year, so this study aims to see the relationship between the variables of Exchange Rate, FDI and GDP to the Trade Balance in Indonesia. The data used is a time series for 43 years (1980-2022) using the Vector Error Correction Model (VECM) method to analyze the relationship and response between variables in the term short and long term. Short-term results show that the Exchange Rate, Foreign Direct Investment (FDI) and Gross Domestic Product (GDP) do not affect the surplus or deficit of Indonesia's Trade Balance. While in the long run, Exchange Rate appreciation has a negative effect on the Trade Balance, the amount of FDI has a positive impact on the Trade Balance, and the amount of Gross Domestic Product (GDP) affects the deficit in the Trade Balance. The use of monetary policy can help stab ilize exchange rates, increase exports through increased foreign investment, maintain the value of exports, and reduce trade deficits. Rephrase